Synthesis, electrochemical, in situ spectroelectrochemical and in situ electrocolorimetric characterization of new metal-free and metallophthalocyanines substituted with 4-{2-[2-(1-naphthyloxy)ethoxy]ethoxy} groups - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The synthesis of novel metal-free and metallophthalocyanines [Ni(II), Zn(II), Co(II), Cu(II)] were prepared by cyclotetramerization of a novel 4-{2-[2-(1-naphthyloxy)ethoxy]ethoxy}phthalonitrile and the corresponding metal salts (NiCl2, Zn(CH3COO)(2), CoCl2 and CuCl2). The structures of the target compounds were confirmed using elemental analysis, IR, H-1 NMR, C-13 NMR, UV-Vis and MS spectral data. Voltammetric and in situ spectroelectrochemical measurements show that while cobalt phthalocyanine complex gives both metal-based and ring-based redox processes, metal-free, and zinc phthalocyanines show only ring-based reduction and oxidation processes. All complexes decomposed and coated on the electrode as non-conductive film at positive potential window of the electrolyte. An in situ electrocolorimetric method has been applied to investigate color of the electro-generated anionic and cationic forms of the complexes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Phthalonitrile; Cyclic voltammetry; Synthesis; Spectroelectrochemistry; Chromaticity diagram; GAS SENSORS; PHTHALOCYANINES; ZN(II); COBALT; COPPER